European Cytokine Network - Yssel, Hans.; SpringerLink (Online service) (Paris : John Libbey Eurotext : Imprint: John Libbey Eurotext.)
The journal that brings together all areas of work involving cytokines. European Cytokine Network is an electronic journal that publishes original articles and abstracts every quarter to provide an essential bridge between researchers and clinicians with an interest in this cutting-edge field. The journal has become a must-read for specialists in the field thanks to its swift publication and international circulation. The journal is referenced in several databases, including Medline, which is testament to its scientific quality. All articles published since 1997 can now be accessed online.
Keywords: Molecular biology; Molecular Medicine